ANALISIS KECEMASAN IBU DENGAN PERAWATAN BAYI BBLR DI RUMAH SAKITDR AHMAD MUCHTAR - Bunga Humaira; Febriniwati Rifdi (Maternal Child Health Care, 2019)
Low weight for infant is one of problem that often occurs in treatment infant when getting birth. The number of low weight for infant becomes the problems for health workers. Around a quarter of low weight for infants die before stable or in 12 hours first of living infant. Result of SDKI 2002-2003 percentages of low weight for infant shows 7.6%. Based on Riskesdas (basic health research) 2007 around 11.5% infant getting birth with low weight lack of 2500 gram (minister health 2008). So, purpose of this research is to know description mothers’ anxiety with treatment low weight for infants. This research is descriptive research, type of the research qualitative method to know description mothers’ anxiety with treatment low weight for infants in Ahmad Muchtar hospital Bukittinggi 2018. This research is started on june 20-august 15 2018. The total respondent is 10 respondents with purposive sampling. In this research is done input aspect, process, output is done by four steps, they are collecting data through interviewing collection, display and drawing. Based on the result of  the research shows that mother who has low weight infant causes anxiety is mothers’ anxiety to see the infant. It is suggested that workers health when giving the information is more skillful and service improvement. Mothers’ anxiety with treatment low weight for infant can be concluded that informant says that the causes of anxiety is the mother feels anxiety and worried toward the infant. Keywords : Maternal anxiety, LBW baby care